VizieR Online Data Catalog: Gaia DR2. Variable stars in CMD (Gaia Collaboration+, 2019) - Gaia Collaboration; Eyer, L.; Rimoldini, L.; Audard, M.; Anderson, R. I.; Nienartowicz, K.; Glass, F.; Marchal, O.; Grenon, M.; Mowlavi, N.; Holl, B.; Clementini, G.; et al. (VizieR Online Data Catalog, 2019)
Time series in the G, BP, and RP bands of the selected field-of-view transits for 224 sources that are not published in Gaia DR2, but are plotted in Fig. 11. An animated version of Fig. 11 is provided online and at https://www.cosmos.esa.int/web/gaia/gaiadr2_cu7. (2 data files).
Keywords: Magnitudes; Stars: variable; Surveys